Recensión de la obra de José María Miranda Boto (prólogo de Tom Shippey). Law, Government, and Society in J.R.R. Tolkien’s Works, Walking Tree Publishers, Zurich - Jena, 2022 - Sánchez-Rodas Navarro, Cristina (e-Revista Internacional de la Protección Social, 2022)
Recensión de la obra de: José María Miranda Boto (prólogo de Tom Shippey). Law, Government, and Society in J.R.R. Tolkien’s Works, Walking Tree Publishers, Zurich - Jena, 2022